2021
DOI: 10.1161/circresaha.121.318346
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Basis of Hypertrophic Cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is a genetic disease of the myocardium characterized by a hypertrophic left ventricle with a preserved or increased ejection fraction. Cardiac hypertrophy is often asymmetrical, which is associated with left ventricular outflow tract obstruction. Myocyte hypertrophy, disarray, and myocardial fibrosis constitute the histological features of HCM. HCM is a relatively benign disease but an important cause of sudden cardiac death in the young and heart failure in the elderly. Patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 159 publications
0
69
0
4
Order By: Relevance
“…Although, increased deposition of collagen I and collagen III in pro-fibrotic tissues is associated with a less compliant cardiac extracellular matrix, collagen I is more fibrillar and dense in composition compared to the weaker and less mature collagen III (Husse et al, 2007;Querejeta et al, 2004). We also showed increased expression of Myh7, which codes for the βmyosin heavy chain, a well-known marker of cardiac hypertrophy (Marian, 2021) that has also been localized to areas of fibrosis in the heart (Pandya et al, 2006). However, we showed that only expression of Col1 was associated with increased RWT.…”
Section: Discussionmentioning
confidence: 65%
“…Although, increased deposition of collagen I and collagen III in pro-fibrotic tissues is associated with a less compliant cardiac extracellular matrix, collagen I is more fibrillar and dense in composition compared to the weaker and less mature collagen III (Husse et al, 2007;Querejeta et al, 2004). We also showed increased expression of Myh7, which codes for the βmyosin heavy chain, a well-known marker of cardiac hypertrophy (Marian, 2021) that has also been localized to areas of fibrosis in the heart (Pandya et al, 2006). However, we showed that only expression of Col1 was associated with increased RWT.…”
Section: Discussionmentioning
confidence: 65%
“…To confirm the presence of the cardioprotective hypertrophy in the early stages after TAC, we performed RNAseq analysis on isolated cardiomyocytes 2 weeks after TAC treatment ( Figure 2A ). Sarcomeric cardiac β-myosin heavy chain gene ( Myh7) has been shown to be associated with myocardial hypertrophy ( 16 , 17 ). Natriuretic Peptide A ( Nppa ) has secreted by cardiac stretch stimulation, and collagen type I alpha 1 Chain ( Col1a1) is a marker of subsequent fibrosis ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most variations occur in genes that are responsible for normal functioning of contractile sarcomeric proteins: troponin I and T, myosin binding protein C, myosin heavy and light chains, α-actin, titin and α-tropomyosin. Nevertheless, in rare cases, variations in non-sarcomeric protein coding genes have also been reported in HCM patients [19]. The genes predominantly related to the HCM development are TNNT2, MYH7, MYBPC3, ACTC1, TPMI, TNNI3, TNNC1, TNNC2, MYL2, MYL3, CSRP3, and MYOZ2 (Figure 2 and Table 1) [20].…”
Section: Molecular Genetics Of Hcmmentioning
confidence: 99%